System-Level Design Methodologies for Telecommunication - Sklavos, Nicolas; Hübner, Michael; Goehringer, Diana; Kitsos, Paris (Springer International Publishing : Imprint: Springer, 2014)
This book provides a comprehensive overview of modern networks design, from specifications and modeling to implementations and test procedures, including the design and implementation of modern networks on chip, in both wireless and mobile applications.  Topical coverage includes algorithms and methodologies, telecommunications, hardware (including networks on chip), security and privacy, wireless and mobile networks and a variety of modern applications, such as VoLTE and the internet of things.  ·         Provides a comprehensive summary of modern networks design, from specifications to implementations; ·         Explains details of different network technologies for telecommunications, including wireless and mobile protocols; ·         Discusses issues of security and privacy as they relate to wireless and mobile networks; ·         Includes coverage of architectures, design, implementation platforms, and optimizations for networks on chip.